At War with Women Military Humanitarianism and Imperial Feminism in an Era of Permanent War - Greenburg, Jennifer (Cornell University Press, 2023)
At War with Women reveals how post-9/11 politics of gender and development have transformed US military power. In the mid-2000s, the US military used development as a weapon as it revived counterinsurgency in Iraq and Afghanistan. The military assembled all-female teams to reach households and wage war through development projects in the battle for "hearts and minds." Despite women technically being banned from ground combat units, the all-female teams were drawn into combat nonetheless. Based on ethnographic fieldwork observing military trainings, this book challenges liberal feminist narratives that justified the Afghanistan War in the name of women's rights and celebrated women's integration into combat as a victory for gender equality. Jennifer Greenburg critically interrogates a new imperial feminism and its central role in securing US hegemony. Women's incorporation into combat through emotional labor has reinforced gender stereotypes, with counterinsurgency framing female soldiers as global ambassadors for women's rights. This book provides an analysis of US imperialism that keeps the present in tension with the past, clarifying where colonial ideologies of race, gender, and sexuality have resurfaced and how they are changing today.